Copper(I)-Mediated Decarboxylative N-Arylation of Dioxazolones: Synthesis of N-Aryl Amides - Park, Jinhwan; Jang, Dongkyu; An, Jihye; Park, Yeongmi; Bae, Hyeonwoong; Kim, Minseok; Lee, Joohyun; Son, Jongwoo (Synlett, 2023)
Dioxazolones, which are potent amide precursors, have been widely explored for the formation of C–N bonds with the help of transition-metal catalysts. Here, we highlight our recent studies on the synthesis of N-aryl amides using dioxazolones and boronic acids in the presence of copper(I) chloride under mild conditions. The versatility of the developed reaction is demonstrated by its wide range of functional-group tolerances as well as the release of nontoxic carbon dioxide. Optimization screenings reveal that a fluorine additive improves the desired reactivity toward the intended transformation. The addition of triphenylphosphine results in an N-acyl iminophosphorane, suggesting the involvement of an N-acyl nitrene intermediate in this transformation.
Keywords: copper catalysis; amides; nitrenes; boronic acids; C–N bond formation